Incipity recenzji muzycznej - ujęcie porównawcze (wybrane zagadnienia) = Music review incipits - a contrastive approach (selected issues) - Majdańska-Wachowicz, Urszula (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The objective of the article is a contrastive genre-based analysis of selected incipits of music review. The material is retrieved from the Polish magazine "Teraz Rock" and the American biweekly "Rolling Stone" (all 2015 issues). The analysis shows that the two magazines in question share many compositional and stylistic similarities. Incipits can inform about the type of music, the artist`s phonographic achievements, or contain biographical elements. The beginning of the music review is a strategic position where the communicative goals of this genre, i.e. information and evaluation are revealed. In addition, the research proves that the incipit of the music review performs a persuasive function as it aims to encourage the reader to continue reading the full text.
Keywords: incipity; genologia kontrastywna; recenzja muzyczna; "Rolling Stone"; "Teraz Rock"; incipits; contrastive genre-based study; music review